THE CONCEPT OF IDEAL LEADER IN AL-GHAZALI’S THOUGHT - Arifin, M. Syamsul (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2020)
Imam Al-Ghazali (1058-111M) was a great Muslim scholar, thinker, scientist and prolific writer has written a lot of thoughts and ideas in various fields of science, including in the field of Islamic law. In light of the scientific credibility of Imam Al-Ghazali in the Muslim world, this article seeks to discuss the concept of the ideal leader in Islamic law according to Imam Al-Ghazali as he offered in his various works: Al-Iqtiṣād fī al-I’tiqād, At-Tibr al-Masbūk fi Nashīhat al-Mulūk, Iḥyā ’Ulumi ad-Dīn, and Fadh’iḥ al-Bātiniyyah wa Fadhā’il al-Mustaẓhiriyyah. While al-Ghazali seemed to offer a different set of criteria across these works, the essential criteria of the ideal leader in his view include: (1) having knowledge and competence, (2) having good religion and morals, (3) physically and mentally healthy, (4) trustworthy (amanah), (5) fair, (6) willing to listen to advice from scholars, and (7) live simply and close to the people.